Objects as culture‐specific referents of color terms in Russian. Issue 6 (26th October 2018) - Griber, Yulia A.; Mylonas, Dimitris; Paramei, Galina V.
Abstract: The present study is an extension of our analysis of Russian basic color terms (BCTs) elicited in a web‐based psycholinguistic experiment. Color samples ( N  = 600) were approximately uniformly distributed in the Munsell color solid. An unconstrained color‐naming method was employed. Native Russian speakers ( N  = 713; 333 males) participated in the study. Among 1422 elicited unique color words, 698 terms (49%) were derived from object names. Here we explore object‐derived non‐BCTs, focusing on broad classes of names referred to objects, categories within these, and the inventory of color terms, as well as their frequency, patterns of derivation, and derivational productivity. Six classes of object referents were identified: flora, fauna, inanimate nature, food and beverages, man‐made objects, body and bodily products. In detail, 20 most frequent object‐derived terms are reported. These are accompanied by analysis of gender differences and representation of the terms' denotata on the Munsell Mercator projection. In addition, Russian object‐derived color terms are related to those in English; discussed are differences between the 2 languages in the color term classes, inventories and incidences. We conclude that Russian object‐derived color terms follow the generic metonymy pattern, that is, signifying color of objects in the speakers' natural environment. The inventory is also language‐specific, reflecting social practices, preferences and views entrenched in the traditional Russian culture. Furthermore, recent extensive development of the inventory signals 2 novel phenomena: marked globalization influence, surfacing as abundant transliteration of English referent loanwords, and noticeable sociolectal diversification that manifests itself by novel evocative color terms, particularly in marketing and advertisement.